A European Minimum Wage : Implications for Poverty and Macroeconomic Imbalances - Detragiache, Enrica; Ebeke, Christian; Jirasavetakul, La-Bhus Fah.; Kirabaeva, Koralai (Washington, D.C. : International Monetary Fund, 2020)
A hypothetical European Minimum Wage (MW) set at 60 percent of each country's median wage would reduce in-work poverty but have limited effects on overall poverty, as many poor households do not earn a wage near MW and higher unemployment, higher prices, and a loss of social insurance benefits may erode direct benefits. Turning to competitiveness, since the MW increase to reach the European standard would be larger in euro area countries with excessive external surpluses, the associated real appreciation should help curb existing imbalances. However, a few countries with already weak external positions would experience an undesirable real appreciation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet